LANGUAGE LEARNING STRATEGIES IN ENGLISH SPEAKING SKILLS: GAINING THE PERSPECTIVE OF NURSING STUDENTS - Fatimah Layba Ibrahim; Heni Nurhaeni; Audi Yundayani; Fiki Alghadari (Universitas Terbuka, 2023)
The use of English in medical contexts is rising globally. The English for nursing purposes assists students meet the requirement by addressing their needs in the context of nursing, particularly their speaking abilities. However, the shift from offline to online learning has an effect on nursing students' opportunity to practice their English-speaking skills. This study attempts to identify the language learning strategies (LLS) that nursing students employ to improve their speaking abilities for vocational objectives. Forty nursing students from an Indonesian nursing academy were the study's respondents. A questionnaire was used to obtain the data. This study found that (1) in the memory LLS, 92.5 percent of students tend to translate Indonesian sentences into English and produce them orally. In addition, they attempt to recall new English terms by pronouncing them; (2) in the cognitive LLS, 95% of them prefer to practice speaking in front of the mirror; (3) in the compensation LLS, 92.5% of them practice catching the other speaker's main point; (4) in the metacognitive LLS, 95% of them correct their mistakes on their own; (5) in the affective LLS, 95% of them encourage themselves to speak; and (6) in the social LLS, 92.5% of the students practice asking the other speaker to clarify what. According to the findings of the study, nursing students demonstrate an appropriate use of LLS, which results in their English acquisition.